A study on the measurement and influencing factors of the urban wastewater treatment efficiency in China based on the superefficiency SBM-Tobit model - Tao, Tingyu; Zhang, Hao; Hu, Zikun (Frontiers in Environmental Science, 2024)
With urbanization acceleration, ensuring urban water use security and sustainable water resource management has become a major global challenge. As a populous country, China faces increasingly severe challenges. Comprehensive and systematic urban wastewater treatment efficiency (UWTE) assessments constitute a prerequisite for addressing this problem. Based on 2011-2021 panel data of 30 Chinese provinces, the superefficiency SBM model was employed for UWTE measurement from national and regional perspectives. ArcGIS software and the Tobit model were adopted to analyse the spatial-temporal patterns and factors influencing UWTE. UWTE in most provinces generally exhibited a fluctuating upward trend, with an uneven east-high and west-low spatial distribution pattern. The decomposition results showed that the low UWTE in the eastern region was mainly constrained by scale efficiency, while in the central region, pure technical efficiency was the primary constraint. The shunt pipeline construction level, load rate, and wastewater treatment scale significantly positively impacted UWTE, while economic scale yielded a negative impact. It is recommended that the Chinese government adjust the outdated constructionwithout-operation model and implement differentiated wastewater treatment policies. It is necessary to vigorously promote rainwater and wastewater diversion pipeline construction, optimize and upgrade sewer networks and wastewater treatment facilities, and fully utilize scale effects. These findings provide insights for China and countries similar to China to facilitate efficient wastewater management practices.